Effects of ultrafine grinding and cellulase hydrolysis separately combined with hydroxypropylation, carboxymethylation and phosphate crosslinking on the in vitro hypoglycaemic and hypolipidaemic properties of millet bran dietary fibre. (30th December 2022) - Zheng, Yajun; Wang, Xueying; Sun, Yue; Cheng, Chaoxia; Li, Junru; Ding, Pan; Xu, Bufan
Abstract: Ultrafine grinding and cellulase hydrolysis separately combined with hydroxypropylation, carboxymethylation and phosphate-crosslinking were used to improve the in vitro hypoglycaemic and hypolipidaemic properties of millet bran dietary fibre (MBDF). Compared to ultrafine grinding and cellulase hydrolysis alone, the three mixed modifications more effectively improved the soluble dietary fibre content, surface area, water-swelling capacity and viscosity of MBDF ( P < 0.05), but reduced the brightness of MBDF. Moreover, MBDF modified by ultrafine grinding, cellulase hydrolysis and carboxymethylation exhibited the highest adsorbing abilities of soybean oil (3.32 g/g), cholesterol (20.75 mg/g) and sodium cholate (72.04 mg/g). MBDF modified by ultrafine grinding, cellulase hydrolysis and phosphate crosslinking demonstrated excellent in vitro hypoglycaemic properties, including glucose-adsorbing ability (4.24 μmol/g) and inhibitory effects on glucose diffusion (74.26%) and α-amylase (62.16%). Additionally, MBDF modified by ultrafine grinding, cellulase hydrolysis and hydroxypropylation exhibited excellent glucose-adsorbing ability (4.90 μmol/g). Therefore, ultrafine grinding, cellulase hydrolysis combined with carboxymethylation and phosphate crosslinking is a good choice to improve the hypolipidaemic properties of MBDF, while ultrafine grinding, cellulase hydrolysis and phosphate crosslinking is a good option for improving the hypoglycaemic properties of MBDF. Graphical abstract: Image 1 Highlights: Ultrafine grind, cellulase and carboxymethyl improved hypolipidaemic effect of MBDF. Grinding, cellulase and phosphate-crosslink enhanced hypoglycaemic property of MBDF. Grinding, cellulase and hydroxypropylation enhanced glucose abiding ability of MBDF. All mixed modifications improved water swelling capacity and viscosity of MBDF. Cellulase with hydroxypropylation reduced cholesterol adsorption capacity of MBDF.